2022
DOI: 10.1128/aac.00886-21
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Associated with Area under the Curve versus Trough Monitoring of Vancomycin in Obese Patients

Abstract: Vancomycin is a first-line agent used in the treatment of methicillin-resistant Staphylococcus aureus ; however, vancomycin is associated with acute kidney injury (AKI). Previous literature demonstrates decreased incidence of AKI using 24-hour area under the concentration-time curve (AUC 24 ) monitoring, but its safety is unknown in obese populations. Patients ≥18 years, with Body Mass Indices (BMI) ≥30 kg/m 2 , admitted between August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…One study was excluded as it was descriptive and used each patient as their own control 24 . After these articles were excluded, 10 studies were included in the primary analysis 25–34 . A full description of the study selection process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was excluded as it was descriptive and used each patient as their own control 24 . After these articles were excluded, 10 studies were included in the primary analysis 25–34 . A full description of the study selection process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the study characteristics is reported in Table 1. Three studies reported significant reductions in AKI with AUC‐guided dosing, 25,27,32 while six studies 26,28–30,33,34 favored AUC‐guided dosing but with nonsignificant results. One study favored trough‐guided dosing, though the results were not statistically significant 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with patients obesity should be cautioned about the risk of overdose when increase in VCM concentrations is anticipated. 30) In particular, VCM dose greater than 4000 mg has been reported to increase the risk of nephrotoxicity. 6,[30][31][32] Previous studies defined patients with BMI > 30 kg/m 2 as obese.…”
Section: Discussionmentioning
confidence: 99%